Impact of Music Education at Colleges of Education on Primary School Pupils in Nanumba North District - Amoah, Charles Agyei; Klutse, Eric Kwadzo; Mawusi, Eddison Foster; Sukpen, Solomon (International Journal of Scientific Research and Management (IJSRM), 2020)
This paper presents how music education in the Colleges of Education influences the teaching of Music and Dance on the primary school. This study aimed to evaluate the training of the student-teachers in preparation to teach Music and Dance as well as to explore the relationship between Music Education at the Colleges of Education and the primary schools. Qualitative method was used and data were obtained through interviews and observations. Fifteen (15) respondents were selected from three (3) schools in the Nanumba North District – Bimbila were randomly sampled for the study. Findings revealed that the amount of training or preparation received in Colleges of Education has been inadequate and has no influence on what entails in the Creative Arts (Music and Dance) syllabus. Hence making teachers handicapped in handling Music and Dance lessons. The work recommends that more attention should be given to teacher preparation in Music and Dance in terms of contents and the methodology to meet the demands of Creative Arts (Music and Dance) syllabus. Also, there should be a revision of subjects that comprise Creative Arts in the Colleges to conform to Creative Arts in the primary school.